Evaluation of static ulcer on lower extremities using wireless wearable near-infrared spectroscopy device: Effect of deep venous thrombosis on TRiggered Angiography Non-Contrast-Enhanced sequence magnetic resonance imaging. (December 2020) - Lin, Bor-Shyh; Chen, Chien-Wei; Zhou, Shao-Kui; Tseng, Yuan-Hsi; Wang, Shih-Chung; Huang, Yao-Kuang
Background: Venous leg ulcers, or static leg ulcers, are chronic wounds associated with ambulatory venous hypertension of the lower extremities as a consequence of venous valve reflux, reduce venous capacitance, poor calf venous pump, heart failure, or in conjunction with venous obstruction. A static ulcer with venous thrombosis in a pelvic or thigh vein responds favorably to anticoagulation agents. However, anticoagulation is less effective and even harmful when ambulatory venous hypertension has another cause such as venous reflux, poorly heart function, and poor calf venous pump. Method: TRiggered Angiography Non-Contrast-Enhanced (TRANCE) magnetic resonance imaging (MRI) exploits differences in vascular signal intensity during the cardiac cycle for subsequent image subtraction, providing detailed radiation-free venograms without the use of contrast agents. The method is a new tool for evaluating the presence of thrombosis in the venous systems. TRANCE-MRI was employed to document the existence of venous thrombosis within the eight patients in this study. Subsequently, we used a wireless wearable near-infrared spectroscopy device to compare deep vein thrombosis-associated and non-deep vein thrombosis-associated static ulcers. The sampling depths were 5 and 10 mm, representing the dermis and subcutaneous tissue, respectively. Result: There are four patients with venous leg ulcers proven with venous thrombosis by TRANCE-MRI and are classified as deep vein thrombosis group. Compared with the non-deep vein thrombosis group, the deep vein thrombosis group had less deoxyhemoglobin, less total hemoglobin, and a significantly lower H2 O signal in the 5-mm sampling depth (dermis level). And eight health participants were included as control group. Wounded patients (including deep vein thrombosis and non-deep vein thrombosis patients) have higher H2 O concentration on the 5-mm depth sampling than control group. In the 10-mm sampling depth (subcutaneous level), the deoxyhemoglobin and tissue oxygen saturation of the deep vein thrombosis group were lower than those of the non-deep vein thrombosis group, and the H2 O concentration was higher than non-deep vein thrombosis group. Patients with static foot ulcers and deep vein thrombosis had similar oxyhemoglobin, deoxyhemoglobin, total hemoglobin, and tissue oxygen saturation than did those without deep vein thrombosis in 5-mm depth sampling (dermis level). Notably, the H2 O signal of patients with non-deep vein thrombosis-associated static ulcers was higher for the 5-mm sampling depth. Conclusion: In patients with static ulcers and deep vein thrombosis, the H2 O level may be higher in the 10-mm sampling depth, indicating that those patients had more subcutaneous water. In patients with non-deep vein thrombosis static foot ulcer, the near-infrared spectroscopy (NIRS) indicated worse fluid retention in the dermis level. The H2 O value in the NIRS may be different owing to underline the cause of the venous leg ulcers.